2021
DOI: 10.1515/hsz-2021-0212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of binding mode of low-sulfated hyaluronan to 3D collagen matrices on its osteoinductive effect for human bone marrow stromal cells

Abstract: Synthetically sulfated hyaluronan derivatives were shown to facilitate osteogenic differentiation of human bone marrow stromal cells (hBMSC) by application in solution or incorporated in thin collagen-based coatings. In the presented study, using a biomimetic three-dimensional (3D) cell culture model based on fibrillary collagen I (3D Col matrix), we asked on the impact of binding mode of low sulfated hyaluronan (sHA) in terms of adsorptive and covalent binding on osteogenic differentiation of hBMSC. Both bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…One of the main selective binding properties of S-HA is its high affinity for different cytokines and growth factors, including fibroblast growth factor (FBG), vascular endothelial growth factor (VEGF), and transforming growth factor-beta (TGF-β) [48]. These growth factors perform important roles in wound healing, tissue repair and angiogenesis, and S-HA capability to selectively bind to, and sequestering these factors can improve their bioactivity and support tissue regeneration [49].…”
Section: Selective Binding Characteristics Of S-hamentioning
confidence: 99%
“…One of the main selective binding properties of S-HA is its high affinity for different cytokines and growth factors, including fibroblast growth factor (FBG), vascular endothelial growth factor (VEGF), and transforming growth factor-beta (TGF-β) [48]. These growth factors perform important roles in wound healing, tissue repair and angiogenesis, and S-HA capability to selectively bind to, and sequestering these factors can improve their bioactivity and support tissue regeneration [49].…”
Section: Selective Binding Characteristics Of S-hamentioning
confidence: 99%
“…The importance of GAG and proteoglycans for hMSC osteogenic differentiation has been investigated in several in vitro studies. [35][36][37][38][39][40][41][42] Synthetically S-HA as used in this study has been previously shown to promote the osteogenic differentiation of hMSC. [35,38,41] S-HA could alter several cellular processes such as cell signaling pathways (e.g., BMP-2 (bone morphogenetic protein-2) and TGF-β1 (transforming growth factor-β1) signaling), proteins involved in endocytosis, cell-ECM interaction, and ECM remodeling as well as matrix vesicle formation and composition.…”
Section: Screening Of Hmsc Attachment Proliferation and Osteogenesis ...mentioning
confidence: 99%